2016
DOI: 10.1101/064832
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An aging-independent replicative lifespan in a symmetrically dividing eukaryote

Abstract: The replicative lifespan (RLS) of a cell-defined as the number of cell divisions before death-has informed our understanding of the mechanisms of cellular aging. However, little is known about aging and longevity in symmetrically dividing eukaryotic cells because most prior studies have used budding yeast for RLS studies. Here, we describe a multiplexed fission yeast lifespan micro-dissector (multFYLM) and an associated image processing pipeline for performing high-throughput and automated single-cell micro-di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 73 publications
(89 reference statements)
1
11
1
Order By: Relevance
“…Thus, if anything, we underestimated the prevalence of the global hotspots as sites for age-associated junction formation. Work in other systems has shown that copy numbers of rDNA repeats decrease with age, and instability in this region is linked with ageing and longevity (Spivey et al 2017;Kobayashi 2014;Lu et al 2018). The decrease of rDNA copy numbers with age could be linked to junction formation in these regions: work in primate kidney cells has demonstrated differential repair of cellular DNA sequences (Zolan et al 1982), reminiscent of the heterogeneity we observe for age-associated rearrangements.…”
Section: Similar Patterns Of Genome Rearrangements Accumulate In Old mentioning
confidence: 57%
See 1 more Smart Citation
“…Thus, if anything, we underestimated the prevalence of the global hotspots as sites for age-associated junction formation. Work in other systems has shown that copy numbers of rDNA repeats decrease with age, and instability in this region is linked with ageing and longevity (Spivey et al 2017;Kobayashi 2014;Lu et al 2018). The decrease of rDNA copy numbers with age could be linked to junction formation in these regions: work in primate kidney cells has demonstrated differential repair of cellular DNA sequences (Zolan et al 1982), reminiscent of the heterogeneity we observe for age-associated rearrangements.…”
Section: Similar Patterns Of Genome Rearrangements Accumulate In Old mentioning
confidence: 57%
“…Ribosomal RNA genes are highly transcribed and common sites of transcription and replication stress (Gaillard and Aguilera 2016; Aguilera and García-Muse 2013). Moreover, rDNA repeats can become unstable during ageing and cause cell death (Spivey et al 2017;Lu et al 2018;Kobayashi 2014).…”
Section: Similar Patterns Of Genome Rearrangements Accumulate In Old mentioning
confidence: 99%
“…Information on how data collected using this methodology is analyzed can be found in these references ( Greenstein et al ., 2017 ; Spivey et al ., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the low-throughput and laborious nature of this assay limits our current understanding of replicative aging. Most recently, removal of progeny cells has been automated in microfluidic devices that capture and retain individual aging cells ( Wang et al ., 2010 ; Lee et al ., 2012 ; Xie et al ., 2012 ; Zhang et al ., 2012 ; Tian et al ., 2013 ; Crane et al ., 2014 ; Nobs and Maerkl, 2014 ; Jo et al ., 2015 ; Liu et al ., 2015 ; Nakaoka and Wakamoto, 2017 ; Spivey et al ., 2017 ). Using such devices, relatively large cohorts of individual cells (100 s to 1,000 s of cells) can then be tracked independently from one another.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation